2015
DOI: 10.3233/jad-141731
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory Role for the Insulin- and BDNF-Linked RORA in the Hippocampus: Implications for Alzheimer's Disease

Abstract: Abstract. Alzheimer's disease (AD) is the leading cause of dementia. The etiology of AD remains, in large part, unresolved. In this study, gene expression (microarray) data from postmortem brains in normal aged as well as AD-affected brains in conjunction with transcriptional regulatory networks were explored for etiological insights. The focus was on the hippocampus, a brain region key to memory and learning. The transcriptional regulatory networks were inferred using a trees-based (random forests or extra-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 58 publications
4
30
0
Order By: Relevance
“…By using psychometric tests of cognitive function, Ersland et al found that there was a strong association between the RORB gene and a test of verbal intelligence [19]. Consistent with this notion, Acquaah-Mensah et al reported that the expression of the RORA gene is distinctly up-regulated in the hippocampi of AD-affected postmortem human brains, a brain region key to memory and learning, indicating a potential link between RORA and AD [20]. In terms of brain cognitive functions such as mood, the RORA gene was reported to increase the risk of acquiring psychiatric and neurological disorders, including bipolar disorder [6], autism spectrum disorder [21], and post-traumatic stress disorder [22].…”
Section: Discussionmentioning
confidence: 99%
“…By using psychometric tests of cognitive function, Ersland et al found that there was a strong association between the RORB gene and a test of verbal intelligence [19]. Consistent with this notion, Acquaah-Mensah et al reported that the expression of the RORA gene is distinctly up-regulated in the hippocampi of AD-affected postmortem human brains, a brain region key to memory and learning, indicating a potential link between RORA and AD [20]. In terms of brain cognitive functions such as mood, the RORA gene was reported to increase the risk of acquiring psychiatric and neurological disorders, including bipolar disorder [6], autism spectrum disorder [21], and post-traumatic stress disorder [22].…”
Section: Discussionmentioning
confidence: 99%
“…RORA is reduced in the brain and lymphoblastoid cell lines of multiple cohorts of individuals with autism spectrum disorder [25]. RORA is specifically upregulated in the Alzheimer's disease (AD) hippocampus and emerges as a gene with a probable central role in AD pathology/etiology [24]. Microdeletions overlapping RORA on 15q22.2 can also lead to epileptic seizures and mild intellectual disabilities [38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a RORα inverse agonist suppresses insulitis and prevents hyperglycemia in a mouse model of type 1 diabetes [ 35 ]. RORα also potentially regulates transcription of brain-derived neurotrophic factor, which is associated with Alzheimer’s disease [ 36 38 ]. Finally, IkappaBzeta cooperates with RORα to regulate the development of T helper 17 cells during inflammation [ 39 42 ].…”
Section: Discussionmentioning
confidence: 99%